1985
DOI: 10.1111/j.1528-1157.1985.tb05660.x
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Learning Differences in Epileptic Patients with Left and Right Temporal Lobe Foci

Abstract: A verbal learning test patterned after and using the same format as the Rey Auditory-Verbal Learning Test was administered to the following three groups: (1) patients with left temporal lobe epilepsy (L-TLE) as defined by EEG criteria (n = 11); (2) patients with right temporal lobe epilepsy (n = 10); and (3) normal controls (n = 11). Performance was highly similar for all three groups during the five immediate recall learning trials. The performance of the L-TLE group, averaged across three delayed recall tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
2
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 21 publications
5
40
2
1
Order By: Relevance
“…This is important because there has been a certain amount of controversy with regard to how well one can identify hemisphere ofepileptic focus by observing memory performance in presurgery patients (Andrewes, Puce, & Bladin, 1990;Delaney, Rosen, Mattson, & Novelly, 1980;Mungas, Ehlers, Walton, & McCutchen, 1985). In this small group of subjects, at least, the tests employed in Experiments 1 and 2 appear to fare quite wen in this regard.…”
Section: Resultsmentioning
confidence: 99%
“…This is important because there has been a certain amount of controversy with regard to how well one can identify hemisphere ofepileptic focus by observing memory performance in presurgery patients (Andrewes, Puce, & Bladin, 1990;Delaney, Rosen, Mattson, & Novelly, 1980;Mungas, Ehlers, Walton, & McCutchen, 1985). In this small group of subjects, at least, the tests employed in Experiments 1 and 2 appear to fare quite wen in this regard.…”
Section: Resultsmentioning
confidence: 99%
“…Functional assessment of MTLE patients using cognitive neuropsychologic measures shows a material specific deficit of verbal memory in patients with left temporal epilepsy, and of visual memory in patients with right MTLE (67)(68)(69)(70)(71)(72). In patients with left MTLE, preoperative verbal memory deficit has been correlated with cell loss in CA3 (73).…”
Section: Developmental Acquired Medial Temporal Lobe Epilepsy Localmentioning
confidence: 99%
“…Other left hemisphere functions can be seen as resources to compensate or substitute for verbal memory impairment. Several studies on patients with temporal lobe epilepsy (TLE) showed that verbal memory, and in particular, short-term memory, is strongly related to verbal capacities and attention (21)(22)(23)(24). These functions can therefore be seen as markers for a patient's ability to compensate behaviorally for verbal learning and memory impairments.…”
mentioning
confidence: 99%